Ethical Leadership and Affective Organizational Commitment: The Direct and Indirect Effects in the Presence of Work Engagement and Supervisor’s Organizational Embodiment - Atteya, Ghada (The Arab Journal of Administration, 2018)
Ethical Leadership is «the demonstration of normatively appropriate conduct through personal actions and interpersonal relationships. and the promotion of such conduct to the followers» (Brown, et al., 2005). Although there is a growing research concerning ethical leadership. Still there is a need to identify the mechanisms and conditions through which ethical leadership can affect the subordinates’ behaviors relying on learning and social exchange theories. The present study aims to investigate the relationship between ethical leadership and affective organizational commitment either directly and indirectly through followers’ work engagement. It also seeks to identify the conditions in which ethical leadership would be more influential on the followers’ behaviors through studying the interaction between ethical leadership and Supervisor’s Organizational Embodiment. Using the Path Analysis on a sample of 393 employees, The results confirmed the hypothesees and showed that ethical leadership is positively related to affective organizational commitment either directly. And indirectly through subordinates’ work engagement (as a mediator). In addition, the relationship between Ethical leadership and work engagement became stronger in condition of the interaction between ethical leadership and Supervisor’s Organizational Embodiment (as a moderator).